Activity Profile of High-Level Australian Lacrosse Players. Issue 1 (January 2015) - Polley, Chris S.; Cormack, Stuart J.; Gabbett, Tim J.; Polglaze, Ted
Abstract : Abstract: Polley, CS, Cormack, SJ, Gabbett, TJ, and Polglaze, T. Activity profile of high-level Australian lacrosse players. J Strength Cond Res 29(1): 126–136, 2015—Despite lacrosse being one of the fastest growing team sports in the world, there is a paucity of information detailing the activity profile of high-level players. Microtechnology systems (global positioning systems and accelerometers) provide the opportunity to obtain detailed information on the activity profile in lacrosse. Therefore, this study aimed to analyze the activity profile of lacrosse match-play using microtechnology. Activity profile variables assessed relative to minutes of playing time included relative distance (meter per minute), distance spent standing (0–0.1 m·min −1 ), walking (0.2–1.7 m·min −1 ), jogging (1.8–3.2 m·min −1 ), running (3.3–5.6 m·min −1 ), sprinting (≥5.7 m·min −1 ), number of high, moderate, low accelerations and decelerations, and player load (PL per minute), calculated as the square root of the sum of the squared instantaneous rate of change in acceleration in 3 vectors (medio-lateral, anterior-posterior, and vertical). Activity was recorded from 14 lacrosse players over 4 matches during a national tournament. Players were separated into positions of attack, midfield, or defense. Differences (effect size [ES] ± 90% confidence interval) between positions and periods of play were considered likely positive when there was ≥75% likelihood of the difference exceeding an ES threshold of 0.2. Midfielders had likely covered higher (mean ± SD ) meters per minute (100 ± 11) compared with attackers (87 ± 14; ES = 0.89 ± 1.04) and defenders (79 ± 14; ES = 1.54 ± 0.94) and more moderate and high accelerations and decelerations. Almost all variables across positions were reduced in quarter 4 compared with quarter 1. Coaches should accommodate for positional differences when preparing lacrosse players for competition.